Association of Self-Reported Coping Strategies With Speech Recognition Outcomes in Adult Cochlear Implant Users. Issue 8 (September 2022) - Espahbodi, Mana; Harvey, Erin; Livingston, Austin J.; Montagne, William; Kozlowski, Kristin; Jensen, Jamie; Liu, Xuerong; Juan, Wanlin; Tarima, Sergey; Rusch, Mark; Harris, Michael S.
Abstract : Objective: To characterize the degree to which individual coping strategies may influence speech perception after cochlear implantation. Study Design: Retrospective cohort study. Setting: Tertiary referral center. Patients: Adult, postlingually deaf cochlear implant recipients. Intervention(s): The Coping Orientation to Problems Experience inventory, a validated, multidimensional self-reported coping scale, was administered preoperatively. Main Outcome Measure(s): Speech perception was measured using consonant-nucleus-consonant (CNC) phoneme and word scores, AzBio sentence accuracy in quiet and noise, and Hearing in Noise Test sentences in quiet preoperatively and at 1, 3, and 6 months postoperatively. Quality of life was measured with the Hearing Implant Sound Quality Index and the Nijmegen Cochlear Implant Questionnaire. Results: Thirty-six patients were included in this study. Mean age at surgery was 70.7 ± 11.4 years. Acceptance was associated with a decreased AzBio in noise score in the 6 months after CI (regression coefficient b = −0.05; 95% confidence interval [CI], −0.07 to −0.03; p < 0.01). Denial was associated with a decreased AzBio in quiet score ( b = −0.05; 95% CI, −0.09 to −0.01; p < 0.05), whereas humor was associated with an increased AzBio in quiet score ( b = 0.02; 95% CI, 0.01 to 0.04; p < 0.05). Humor was also associated with an increased Hearing in Noise Test score ( b = 0.05; 95% CI, 0.02 to 0.07; p < 0.05). Denial was associated with decreased CNC word ( b = −0.04; 95% CI, −0.06 to −0.02; p < 0.01) and phoneme ( b = −0.04; 95% CI, −0.07 to −0.02; p < 0.01) scores, whereas substance use was associated with increased CNC word ( b = 0.03; 95% CI, 0.01 to 0.05, p < 0.01) and phoneme ( b = 0.04; 95% CI, 0.02 to 0.06; p < 0.01) scores. Scores on self-reported quality of life measures were not significantly correlated with coping strategies. Conclusion: A variety of adaptive and maladaptive coping strategies are used by postlingually deaf adult cochlear implant users. Denial and acceptance may be more predictive of poor speech performance, whereas humor and substance use may be more predictive of improved speech performance.